Potential of Longan Seed Extract–Loaded Alginate–Chitosan Beads as Drug Delivery System - Buntum, Tanawat; Kakumyan, Pattana; Surassmo, Suvimol; Thanomsilp, Chuleeporn; Suwantong, Orawan (Frontiers in Materials, 2022)
The potential of drug delivery system of longan seed extract (LSE) incorporated in the alginate/chitosan (Alg/CS) beads has been studied. The LSE-loaded Alg/CS beads were prepared by ionic gelation method via interaction between the protonated amino groups of CS and negatively charged carboxylic groups of Alg. Properties of the LSE-loaded Alg/CS beads were investigated including morphology of the beads, particle sizes, encapsulation efficiency (%EE), controlled release profile, cytotoxicity, and biocompatibility. SEM images of the LSE-loaded Alg/CS beads showed spherical shapes, rough surfaces with some aggregation. The particle sizes were between 1900 to 2600 nm with the PDI values of 0.1503 to 0.3183. Encapsulation efficiencies were between 11 to 18%. Cytotoxicity and biocompatibility tests showed that the beads were non-toxic to both NCTC clone 929 and NHDF cells and promoted the attachment of NHDF cells. Thus, these beads could be used as polymeric drug carriers.